Insight into the complexities of human nutrition and holistic health: the value of qualitative descriptive research - Cornelia Potterie; Herculina S Kruger; Mieke Faber; Hannah Ricci (The South African Journal of Clinical Nutrition)
South Africa’s nutrition transition, driven by a complex interplay of socio-ecological factors, has led to rapidly rising rates of overweight, obesity and non-communicable diseases. While quantitative methods offer important insights, they cannot fully capture these multifaceted issues. Qualitative descriptive research, rooted in naturalistic inquiry, provides both exploratory and explanatory value with procedural simplicity in illuminating the complexities of human nutrition and holistic health in South Africa, guiding the development of more effective and culturally sensitive interventions and policies. Recommendations are offered for future research using qualitative descriptive methods to enhance our understanding of the nutrition transition and its broader health implications.